Communicating About Water in the Floridan Aquifer Region: Part 5—Increasing Collaboration Between Producers and Environmentalists on Water Challenges: AEC788/WC449, 3/2024 - Hundemer, Sadie; Ramadan, Shenara (EDIS, 2024)
<!--StartFragment --> In the Floridan Aquifer region, agricultural producers (farmers and ranchers) and environmentalists are essential water stakeholders, yet they are often perceived to be in conflict over water management. This perceived conflict could be a major impediment to future water policy action. Recent research examined whether there are areas of agreement that could unite producers and environmentalists in support of mutually beneficial water management strategies. A 2017–2018 study found substantial similarities of water priorities between producers and environmentalists despite some areas of disagreement. Capitalizing on shared interests could provide water communicators with a strong basis for developing partnerships and addressing areas of dispute. <!--EndFragment -->